Pain propagation in the carpal tunnel syndrome: a quantitative sensory testing - Tatjana Bućma; Igor Sladojević (Medicinski glasnik, 2024)
Aim: To determine the existence of damage to thin sensitive fibres (A? and C) by quantitative sensory testing (QST) in female patients with carpal tunnel syndrome (CTS), the existence of pain, and a connection with the in-nervation field of the nerve itself. Methods: Forty-two consecutive female patients with symptoms of CTS participated in the research. According to the clinical findings and electroneurography they were divided into group I of 22 women with confirmed CTS and group II of 20 women with non-confirmed disease. Using QST, the threshold of heat and cold, and the threshold of pain caused by heat and cold on the thenar, second, and third finger of the dominant hand in both groups was determined. Results: There was a statistically significant difference in group I for the threshold of heat and cold detection and the threshold of pain caused by heat and cold between the thenar and the fingers. In the group II, there was a statistically significant difference in the threshold of heat detection between the thenar and the fingers. There was a statistically significant difference between the groups in the threshold of heat and cold detection on the fingers and the threshold of pain induced by heat on the fingers. Conclusion: In the carpal tunnel syndrome, there was damage to thin A? and C fibers in the innervation field of the median nerve, which causes pain within the innervation field of the nerve, but also outside it, which can most likely be a consequence of brain plasticity and central sensitization.
Keywords: diagnosis; median nerve; thermosens-ing; unmyelinated nerve fibre